Organic–Inorganic Eu3+/Tb3+ codoped hybrid films for temperature mapping in integrated circuits - Brites, Carlos; Pereira, Patricia; João, Nuno; Millán, Angel; Amaral, Vitor; Palacio, Fernando; Carlos, Luís A. (Frontiers in Chemistry, 2013)
The continuous decrease on the geometric size of electronic devices and integrated circuits generates higher local power densities and localized heating problems that cannot be characterized by conventional thermographic techniques. Here, a self-referencing intensity-based molecular thermometer involving a di-ureasil organic-inorganic hybrid thin film co-doped with Eu3+ and Tb3+ tris(β-diketonate) chelates is used to obtain the temperature map of a FR4 printed wiring board with spatio-temporal resolutions of 0.42 μm/4.8 ms.